SUBJECTS OF PUBLICATIONS IN THE FIELD OF POLITICAL GEOGRAPHY IN UKRAINE DURING 1990-2012 YEARS - STAFIICHUK, Valentyn (Ekonomichna ta Sotsialna Geografiya, 2015)
Since 1990, the Ukrainian political geography is passing through the latest stage of its development: the number of political and geographical publications were significantly increased and their content was expanded. Based on scientometric analysis of the main geographical magazines of Ukraine during 1900-2012 years 368 articles with political and geographical content were found. The topics of publications in the field of political geography is rather broad and relatively balanced. Almost 50% of articles are devoted to the history of political geography, political geography of Ukraine, electoral geography, the theory and methodology of political geography and political geography of individual regions. The widest range of topics are covered in the “Journal of the Lviv University. Geographical Series” and the scientific book “Geography and Tourism”.

З 1990 року українська політична географія переживає новітній етап свого розвитку: значно збільшилася чисельність і розширився зміст політико-географічних публікацій. На основі проведеного наукометричного аналізу провідних географічних часописів України за 1900-2012 роки було виявлено 368 статтей політико-географічного змісту. Тематика політико-географічних публікацій є досить широкою і відносно збалансованою. Майже 50% статтей присвячені історії політичної географії, політичній географії України, електоральній географії, теорії і методології політичної географії та політичній географії окремих регіонів. Найбільш широкий спектр тем висвітлено у «Віснику Львівського університету. Серія географічна» та науковому збірнику «Географія та туризм».
ТЕМАТИКА ПОЛІТИКО-ГЕОГРАФІЧНИХ ПУБЛІКАЦІЙ В УКРАЇНІ ЗА 1990-2012 РОКИ
Keywords: political geography; publication in the field of political geography; special edition; subjects of articles; політична географія; політико-географічна публікація; фахове видання; тематика публікацій